Service-Oriented Crowdsourcing Architecture, Protocols and Algorithms - Schall, Daniel; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
At a fundamental level, service-oriented crowdsourcing applies the principles of service-oriented architecture (SOA) to the discovery, composition and selection of a scalable human workforce. Service-Oriented Crowdsourcing: Architecture, Protocols and Algorithms provides both an analysis of contemporary crowdsourcing systems, such as Amazon Mechanical Turk, and a statistical description of task-based marketplaces. The book also introduces a novel mixed service-oriented computing paradigm by providing an architectural description of the Human-Provided Services (HPS) framework and the application of social principles to human coordination and delegation actions. Finally, it examines previously investigated concepts and applies them to business process management integration, including the extension of XML-based industry standards and the instantiation of flexible processes in crowdsourcing environments. Service-Oriented Crowdsourcing is intended for researchers and other academics as an in-depth guide to developing new applications based on crowdsourcing platforms and evaluating various selection and ranking algorithms. Practitioners and other industry professionals will also find this book invaluable.
Introduction -- Crowdsourcing Task Marketplaces -- Human-Provided Services -- Crowdsourcing Tasks in BPEL4People -- Conclusion.
Keywords: Computer science; Data mining; Information storage and retrieval systems; Computer Science; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery